PERAN ISLAM DALAM PERKEMBANGAN TEKNOLOGI PENDIDIKAN - Hasibuan, Nasruddin (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2014)
This paper aims to determine the role of Islam in educational technology. Method used in this paper is the method of literature research . Islam is the main role in the development of educational technology are at least 2 (two). First, make the Islamic Aqeedah as the paradigm of thought and science. Thus, the paradigm of Islam, rather than the secular paradigm, which should be taken by Muslims in building the structure of science. Secondly, making use of Islamic law as the standard of science and technology.